2015
DOI: 10.1021/acs.molpharmaceut.5b00785
|View full text |Cite
|
Sign up to set email alerts
|

Lipophilic Prodrugs of SN38: Synthesis and in Vitro Characterization toward Oral Chemotherapy

Abstract: SN38 (7-ethyl-10-hydroxy camptothecin) is a potent anticancer agent belonging to the camptothecin family; however, its oral delivery is extensively restricted by poor solubility in pharmaceutically acceptable excipients and low transmucosal permeability. Lipid-based carriers are well-known for their ability to improve oral absorption and bioavailability of lipid soluble and highly permeable compounds. Thus, this study has focused on improving solubility in lipid excipients, controlling stability, and enhancing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 44 publications
(74 reference statements)
1
59
0
Order By: Relevance
“…Lymphatic targeted delivery of antitumor agents has the potential to treat metastatic malignancies. 65,66 …”
Section: Advantages Of Lipid–drug Conjugatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Lymphatic targeted delivery of antitumor agents has the potential to treat metastatic malignancies. 65,66 …”
Section: Advantages Of Lipid–drug Conjugatesmentioning
confidence: 99%
“…An antitumor agent, SN38, was modified to improve its oral delivery by attaching undecanoate (C20). 66 The formation of lipophilic prodrug led to the increase in the uptake of drugs in enterocytes, resulting in more than doubled increase in drug permeation through the intestinal epithelium of rats.…”
Section: Advantages Of Lipid–drug Conjugatesmentioning
confidence: 99%
“…The lymphatic system presents a reservoir for human immunodeficiency virus (HIV), such that the majority of HIV replication occurs in the intestinal lymphatic tissues . Examples of lymphatic‐targeted prodrugs designed to exploit this pathway include γ‐aminobutyric acid (GABA), TG‐MPA, chlorambucil, melphalan, closantel, SN‐38 (7‐ethyl‐10‐hydroxy camptothecin) …”
Section: Physiological Pathways Of Lipid Processingmentioning
confidence: 99%
“…It is the active metabolite of Irinotecan (CPT-11), which is a topoisomerase I inhibitor and is available commercially as Camptosar® [21][22][23] . It has poor aqueous solubility and poor oral bioavailability (8%) 24 . It is formed in the liver and tumors from CPT-11 but its metabolic conversion rate is less than 10% of the original volume of CPT-11 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Folatereceptor-targeted SN-38 NPs was produced earlier using PLGA NPs covalently bound to Poly (ethylene glycol)-folate, which demonstrated more cytotoxicity on HT-29 cells as compared to control NPs [28][29][30] . These nanoparticles where given via the intravenous route and showed that the bioavailability of SN-38 was significantly increased 24,31 . However, oral delivery of nanoparticles is more practical as compared with the intravenous route because of greater convenience, cheaper cost, better patient compliance and further simplicity for long-standing treatment of chronic diseases 9,[32][33][34] .…”
Section: Introductionmentioning
confidence: 99%